2011
DOI: 10.1371/journal.pone.0019981
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Threshold Rule Is Sufficient to Explain Sophisticated Collective Decision-Making

Abstract: Decision-making animals can use slow-but-accurate strategies, such as making multiple comparisons, or opt for simpler, faster strategies to find a ‘good enough’ option. Social animals make collective decisions about many group behaviours including foraging and migration. The key to the collective choice lies with individual behaviour. We present a case study of a collective decision-making process (house-hunting ants, Temnothorax albipennis), in which a previously proposed decision strategy involved both quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 73 publications
7
80
0
Order By: Relevance
“…Specifically, if the quality assessments of individuals are influenced by experience, this would stop workers from being locked into repeatedly rejecting a nest that they deemed poor, even though it constituted the only viable option. Furthermore, as supported by previous experimental and modelling results, experiential influence would also help to ensure that even when multiple options of very high quality were present, the best nest would still be preferred [20,36].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Specifically, if the quality assessments of individuals are influenced by experience, this would stop workers from being locked into repeatedly rejecting a nest that they deemed poor, even though it constituted the only viable option. Furthermore, as supported by previous experimental and modelling results, experiential influence would also help to ensure that even when multiple options of very high quality were present, the best nest would still be preferred [20,36].…”
Section: Discussionmentioning
confidence: 70%
“…Previous work has shown that ants can choose between nests without directly comparing them, and thus save both time and cognitive effort [9]. The exact mechanism underpinning such decentralized nest choice remains unclear, but it has been hypothesized that workers may have considerable variation in their individual quality thresholds, each accepting a nest option only if it meets their individual 'quality standards' [20,21]. For this system to be effective, however, differing worker quality assessments would need to be flexibly distributed within colonies, in order to ensure the best possible emigration decisions, and avoid the pitfalls of becoming locked into suboptimal choices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scout B will then make an independent assessment of the nest, and will either reject it and keep searching, or accept the nest and spend some time in it, before returning home and recruiting a further scout. By this positive feedback process, a good quality nest will accumulate ants [34], [36]. Different ants appear to have differing thresholds for starting recruitment to a nest; this means that even low quality nests can attract some ants, but scouts will accumulate more quickly and to a higher level at higher quality nests [39] [35].…”
Section: Collective Decision-making In House Hunting Antsmentioning
confidence: 99%